2019
DOI: 10.1212/wnl.0000000000006956
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of cortical superficial siderosis in cerebral amyloid angiopathy

Abstract: ObjectiveTo investigate the prognostic relevance of cortical superficial siderosis (cSS) in patients with cerebral amyloid angiopathy (CAA).MethodsA total of 302 patients fulfilling clinical and imaging criteria for probable or possible CAA were enrolled into a prospective, multicenter cohort study and followed for 12 months. cSS was assessed on T2*/susceptibility-weighted imaging MRI. The predefined primary composite endpoint was incident stroke or death in patients with cSS compared to those without. Seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 19 publications
1
42
0
Order By: Relevance
“…Previous literature has suggested that cSS represents a more severe stage of CAA [9] and is associated with amyloid positivity in patients with probable CAA [10]. However, to the best of our knowledge, there is no data available analyzing the distribution of cSS in association with local amyloid positivity and there is no data at all on cSS and tau pathology.…”
Section: Discussion/conclusionmentioning
confidence: 89%
“…Previous literature has suggested that cSS represents a more severe stage of CAA [9] and is associated with amyloid positivity in patients with probable CAA [10]. However, to the best of our knowledge, there is no data available analyzing the distribution of cSS in association with local amyloid positivity and there is no data at all on cSS and tau pathology.…”
Section: Discussion/conclusionmentioning
confidence: 89%
“…Hemorrhagic manifestations of SVD include microbleeds, larger intracranial hemorrhages, focal subarachnoid hemorrhage, and cortical superficial siderosis. The latter is tightly linked to CAA and has prognostic relevance (98).…”
Section: Imagingmentioning
confidence: 99%
“…In CAA, Aβ40 predominantly deposits in the smooth muscle cell layers of leptomeningeal/cortical arteries and capillaries, 22‐25 which is exacerbated in males and in apolipoprotein E ( APOE ) ε4 carriers in AD 21 . CAA is responsible for ∼20% of cerebral hemorrhage cases in the elderly and increases the risk of hemorrhage as assessed by MRI 20,26 . Although BBB damage and CAA are main cerebrovascular phenotypic features frequently observed in AD, their relationship is not precisely understood.…”
Section: Introductionmentioning
confidence: 99%